Faith of my fathers : a family memoir - McCain, John, 1936-2018.; Salter, Mark. (New York : HarperPerennial, 2000)
Congressman John McCain explains how he learned about life and honor from his grandfather and father, both four-star admirals in the U.S. Navy.
Originally published: New York : Random House, 1952.
Keywords: McCain, John, -- 1936-2018 -- Religion; McCain, John, -- 1936-2018 -- Family; United States. -- Congress. -- Senate -- Biography; McCain, John S. -- 1911-1981.; McCain, John Sidney, -- 1884-1945.; United States. -- Navy -- Biography; Legislators -- United States -- Biography; Fathers -- United States -- Biography; Grandfathers -- United States -- Biography; Grandfathers -- United States -- Biography; Fathers -- United States -- Biography; Biography